2015
DOI: 10.1103/physrevlett.115.046802
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Emission from Hybridized States in a Semiconductor Charge Qubit

Abstract: We explore the microwave radiation emitted from a biased double quantum dot due to the inelastic tunneling of single charges. Radiation is detected over a broad range of detuning configurations between the dot energy levels, with pronounced maxima occurring in resonance with a capacitively coupled transmission line resonator. The power emitted for forward and reverse resonant detuning is found to be in good agreement with a rate equation model, which considers the hybridization of the individual dot charge sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
89
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(94 citation statements)
references
References 38 publications
5
89
0
Order By: Relevance
“…Few examples of hybrid quantum systems include cavity-Quantum Electrodynamics (c-QED) arrays [2,[5][6][7], cold atoms coupled to light [8][9][10], optomechanical devices [11,12] and cavity-coupled quantum dots [2,[13][14][15][16][17][18][19][20][21]. The motivation for this paper is a class of recent experiments where quantum dots have been integrated with superconducting resonators, accomplishing sufficiently strong charge-cavity coupling of g ∼ 50 − 200 MHz [13,[22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Few examples of hybrid quantum systems include cavity-Quantum Electrodynamics (c-QED) arrays [2,[5][6][7], cold atoms coupled to light [8][9][10], optomechanical devices [11,12] and cavity-coupled quantum dots [2,[13][14][15][16][17][18][19][20][21]. The motivation for this paper is a class of recent experiments where quantum dots have been integrated with superconducting resonators, accomplishing sufficiently strong charge-cavity coupling of g ∼ 50 − 200 MHz [13,[22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Recent experiments confirmed that JPAs [5] and a Josephson traveling-wave parametric amplifier [6] can work near the quantum limit and can be used for a wide range of applications. These include generation of squeezed microwave fields [5,[7][8][9], measurement of a displacement of a nanomechanical oscillator [10,11], implementation of the high-fidelity single-shot measurement [12][13][14][15], quantum feedback [16,17], and feed-forward [18] for superconducting qubits, generation of the two-mode squeezed states of microwave photons [19] as well as read-out of double quantum dots [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…5 we illustrate the dependence of the lasing peaks on the tunneling strength t. Such a dependence was also checked in the experiments with single-level double quantum dots by Stockklauser et al 24 . They found that with stronger tunneling strength the hybridization of the levels leads to a merging of the resonance peaks.…”
Section: B Dependence On Further Parametersmentioning
confidence: 72%
“…Also double quantum dot (DQD) systems coupled to a microwave oscillator have been investigated already, both in theory [14][15][16][17][18][19] as well as in experiments [20][21][22][23][24][25][26] . By appropriately tuning the level structure of the DQD system with a single level each, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%